MEMBANGUN SISTEM INFORMASI GEOGRAFIS (SIG) BERPARADIGMA QUR’ANI - Muhammad Faisal (El-QUDWAH, 2008)
GIS ( Geographical Information System) be organization pool hardware, computer software and geographical data design efficiently in taking, saving,updating, manipulation, analyses and presents all part of geographical information. Geographical yields region map. At era now Peta region have been tidy and diolah into a computer peripheral, this komputrer peripheral which will analyse existing of a place and arranges it by corresponding to model representing the original. Increasinglyly berkembangya research about regional map especially in information technology area, finally is formed an geographical information system. This system of course can give certainty of the decision takers about settlement of region ( region mapping). If evaluated from a real far flung Indonesia state region, hence would hardly requires a GIS which is accurate and precise, why that way? because very very vital position of GIS a region / area having extraordinary effect to pursue existence of events of disaster which bia ought to be prevented early possibly. Why Indonesia region that way respects reputedly overseas, but simply happened a lot of disaster that is still not after, disaster coming silih to change, altogether having element at one particular nature phenomenon which we might not take care of reallyly and serious. Of course settlement of the region needs existence of involvement various party(sides to manage it, but in reality a lot of Iameness happened, why the Iameness Iameness happened, possibly this happened because basis nation believe we still weakening and hardly unable to esteem nature. Result of this research proves that we must be wise wise and in managing nature.Keyword : GIS, nature phenomenon